IRSHĀD AL-FUHŪL ILA TAHQĪQ AL-HAQ MIN ‘ILM AL-UŞŪL KARYA AL-SHAWKANI: PRODUK LOKAL BERWAWASAN GLOBAL - Afif, Abdullah (Irtifaq, 2014)
Al-Shawkani is a local schoolar with global perspective. This is evidenced by the strong tradition surrounding Zaydiyyah intellectual life and his education in around Yemen only. But his thinking has broken boundaries. His famous work in usul al-fiqh is Irshad Fuhūl Ila al-Haq Tahqīq Min 'Ilm al-Usul. This book is one of the book Usul al-Fiqh that can be used as a reference in the study of comparative Usul al-Fiqh. In this book not only explained about the rules of Usul al-Fiqh in the school, but also reveal the rules and understanding with regard to the method istinbāţ and istidlāl of many schools. Style of thinking that is not fanatical and radical that makes his work widely accepted by many people, including Sunni groups Keyword: Al-Shawkani, Irshād al-Fuhūl Ila Tahqīq al-Haq Min „Ilm al-Uşūl